Why Me? To Be an Ultra-Responder to Antiplatelet Therapy: A Case Report - Rosafio, Francesca; Bigliardi, Guido; Lelli, Nicoletta; Vandelli, Laura; Naldi, Federica; Ciolli, Ludovico; Meletti, Stefano; Zini, Andrea (Frontiers in Neurology, 2021)
Background. Platelet function testing is a valid tool to investigate the clinical response to antiplatelet therapy in different clinical settings; particularly it might supply helpful information in patients with cerebrovascular disease. Oral antiplatelet treatment, as Aspirin (ASA) and Clopidogrel, is the gold standard in secondary stroke prevention of non-cardiogenic ischemic stroke; conversely, its application as primary prevention therapy is not routinely recommended in patients with vascular risk factors. Multiple Electrode Platelet Aggregometry (MEA) impedance aggregometer is a validated device to test platelet inhibition induced by ASA or Clopidogrel. Case report. We report a case of a 78 years old patient without relevant clinical history, taking ASA as primary prevention strategy, who was admitted for sudden onset of dysarthria and left facial hyposthenia during physical effort. Brain CT revealed two small subcortical bilateral spontaneous intracranial hemorrhages. Platelet aggregometry with MEA performed at the admission revealed a very strong platelet inhibition induced by ASA (result of ASPI Test was 5 U, consistent with an ultra-responsiveness to ASA, cut-off value of correct responsiveness is <40 U). MRI at longitudinal follow-up revealed the presence of two small cavernous angioma underlying hemorrhagic spots. Conclusion. The evaluation of platelet reactivity in stroke patients undergoing antiplatelet therapies, not commonly performed in clinical practice, could be useful to optimize prevention strategies; the verification of the biological effectiveness of ASA or Clopidogrel could be a valid tool in the definition of each patient’s risk profile, particularly in patients with cerebrovascular disease known to be at increased risk for both hemorrhagic and thrombotic complications.